The Effect Of Using Roundtable Technique Toward Students’ Ability In Writing Hortatory Exposition Text At The Eleventh Grade Students Of SMA NEGERI 9 Mandau - Liasna Br. Sembiring (Jolly Journal of English Education, 2025)
This study was carried out find out the effect of using roundtable technique toward students' ability in writing hortatory exposition text at the eleven grade students of SMAN 9 Mandau. Quantitative descriptive method was used to describe the data, with a quasi-experimental research design. The population of the study was all 296 students in grade XI consisting of 9 classes. Due to the large population, the researcher took a sample of 58 students. In this study, the average pre-test score of the experimental class was 64.72 and the control class was 59.52. While the average post-test score of the experimental class was 77.69 and the control class was 69.10. Based on the probability scores gathered from SPSS 22, it was shown that the sig. (2-tailed) value for Pair 1 was 0.000 < 0.05. This indicated that there were significant differences in the average students’ ability in writing between the pre-test and post-test. This meant that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It could be concluded that there was an effect of by using the Roundtable Technique on students’ ability in writing at the eleventh grade students of SMAN 9 Mandau.